(untitled) (Indonesian Journal of Science and Technology, 2025)
The microwave-assisted pyrolysis (MAP) application of rice straw as feedstock is the primary focus of this research. Some of the solvents that were utilized for soaking feedstocks included benzene, acetone, and ethanol. These solvents were used to pre-treat the rice straw. Through the use of solvents, yields were increased, reaction times were decreased, and the pyrolysis index was improved. KOH catalyst increased the amount of gaseous products produced by 47.5 wt%. When rice straw was prepared with benzene, the average heating rate decreased to 21.8 °C/min, significantly increasing the amount of oil and char produced. Rice straw that had been prepared with acetone had a much lower energy consumption in MAP (283 kJ) when compared to fresh rice straw, which had a different energy consumption (418 kJ). In the process of pyrolysis, it is demonstrated that solvent soaking occupies a significant position. The recovered bio-oil also included mono-aromatics, poly-aromatics, and oxygenated compounds.